1989
DOI: 10.1111/j.1525-1470.1989.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Common Sexually Transmitted Diseases in Adolescents: A Review

Abstract: Sexually transmitted diseases (STDs) represent a significant health problem for adolescents in the United States. As a result, clinicians from a number of disciplines, among them pediatrics and dermatology, may be called on to evaluate teenage patients with these infections. Traditionally, the diagnosis of many STDs has relied on isolation of the causative organisms in culture. While such procedures typically offer optimal diagnostic accuracy, they are often time consuming and expensive, and may not be widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The high prevalence rate of infection amongst traders 12(18.5%) agrees with the findings of Sam-wobo et al (2012) which might be associated with sexual activeness as well as exposure to factors such as poor sanitary facilities, shared usage of toiletries that are characteristic of most trading centers in this part of the country. Trichomoniasis is believed to be transmitted usually through unprotected sexual intercourse, however, some infections probably are acquired through fomites such as towels, toilet seats, and sauna benches which serve as reservoir host (Krowchuk et al, 1989). Majority of the infected patients in our study reported using unimproved sanitary facilities such as public toilets, even among those that use private toilets, shared usage is predominant.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence rate of infection amongst traders 12(18.5%) agrees with the findings of Sam-wobo et al (2012) which might be associated with sexual activeness as well as exposure to factors such as poor sanitary facilities, shared usage of toiletries that are characteristic of most trading centers in this part of the country. Trichomoniasis is believed to be transmitted usually through unprotected sexual intercourse, however, some infections probably are acquired through fomites such as towels, toilet seats, and sauna benches which serve as reservoir host (Krowchuk et al, 1989). Majority of the infected patients in our study reported using unimproved sanitary facilities such as public toilets, even among those that use private toilets, shared usage is predominant.…”
Section: Discussionmentioning
confidence: 99%